Diabetes distress in young adults with early‐onset Type 1 diabetes and its prospective relationship with HbA1c and health status. Issue 7 (25th March 2019) - Stahl‐Pehe, A.; Glaubitz, L.; Bächle, C.; Lange, K.; Castillo, K.; Tönnies, T.; Yossa, R.; Holl, R. W.; Rosenbauer, J.
Abstract: Aim: This study aimed to determine cross‐sectional relationships between diabetes distress and health‐related variables, and prospective associations between diabetes distress and future glycaemic control (HbA1c ) and health status among young adults with early‐onset Type 1 diabetes. Methods: Data were collected from a nationwide cohort study of adults whose Type 1 diabetes onset occurred from 0 to 4 years of age during 1993–2002. Questionnaire surveys were conducted in 2012–2013 and 2015–2016 ( N  = 584). Diabetes distress was assessed via the Problem Areas in Diabetes (PAID) scale (0–100 points), depressive symptoms via the Patient Health Questionnaire‐9 (PHQ‐9) and health status via the 12‐Item Short Form Health Survey (SF‐12) questionnaire. Multivariable linear regression analyses were applied to cross‐sectional and longitudinal data. Results: In the cross‐sectional analyses, higher PAID scale total scores (representing higher distress levels) were observed in women than in men and in participants with more severe depressive symptoms. PAID scores were lower in individuals with better physical and mental health. A 1 mmol/mol increase in HbA1c was associated with a 0.28‐point increase [95% confidence interval (95% CI) 0.20, 0.36] in diabetes distress. In longitudinal analyses adjusting for age, sex, socio‐economic index and HbA1c at baseline, a 10‐point higher PAID score at baseline was associated with a 1.82 mmol/mol higher HbA1c level (95% CI 0.43, 3.20) and a 2.48‐point lower SF‐12 mental health score (95% CI −3.55, −1.42) three years later. Conclusions: The cross‐sectional and longitudinal analyses results suggest that diabetes distress impairs health‐related outcomes in young adults with early‐onset diabetes. What's new?: Diabetes distress is an important psychosocial concern in people with diabetes, but it remains largely unexplored in young adults with early‐onset Type 1 diabetes. Our findings demonstrate associations between diabetes distress and sociodemographic characteristics (sex and socio‐economic status) and important health‐related outcomes (HbA1c, health status and depressive symptoms) in a cohort of young adults with early‐onset Type 1 diabetes. Cross‐sectional analysis indicates that interventions against diabetes distress should particularly target women and young adults with lower socio‐economic statuses, higher HbA1c, impaired satisfaction with care, worse health status and depressive symptoms.